Highly durable fuel cell catalysts using crosslinkable block copolymer-based carbon supports with ultralow Pt loadings. Issue 12 (6th August 2020) - Choi, Juhyuk; Lee, Young Jun; Park, Dongmin; Jeong, Hojin; Shin, Sangyong; Yun, Hongseok; Lim, Jinkyu; Han, Junghun; Kim, Eun Ji; Jeon, Sun Seo; Jung, Yousung; Lee, Hyunjoo; et al.
Abstract : The catalyst in which carbon shells encapsulate PtFe nanoparticles shows superior activity and durability for proton exchange membrane fuel cells. Abstract : Minimizing the use of Pt catalysts in proton exchange membrane fuel cells (PEMFCs) is important, considering its high price and scarcity. Herein, we demonstrate novel catalysts for PEMFCs with exceptionally high mass activity and durability, in which block copolymer-based carbon supports are loaded with an ultra-small amount of Pt. The mass activity measured after 30 000 cycles of single cell tests was 0.81 A mgPt −1 at 0.9 V, which is the highest performance reported to date. The newly developed catalyst yielded nearly the same power density as that of the commercial Pt/C, even with 1/20 of the Pt usage. The carbon supports were prepared by carbonizing crosslinked domains of block copolymer particles selectively, resulting in mesoporous carbon particles with ∼25 nm pores. When Pt was deposited, thin carbon shells were formed encapsulating PtFe nanoparticles, catalyzing the oxygen reduction reaction efficiently with high durability.